2020
DOI: 10.3390/f11101045
|View full text |Cite
|
Sign up to set email alerts
|

Root Exudation Rates Decrease with Increasing Latitude in Some Tree Species

Abstract: Research Highlights: Understanding of the spatial variation of root exudation on a regional scale can help understand the response of plant physiological activities to environmental changes. Background and Objectives: Although root exudation has become an important topic in belowground ecology, its relationship with root traits and environmental factors is poorly understood. Our objective was to explore how root traits and environmental factors influence root exudation. Materials and Methods: We used a multi-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…These results suggest that the environmental conditions impacted the variations in the allelochemical exudation processes from the roots of the two weeds in response to mowing and varying trampling pressure. Similar to the outcome of this study, Yang et al [71] also reported that the root exudation rate of some plant species, such as Pinus koraiensis, Larix gmelinii, and Betula platyphylla, was influenced by environmental factors, including the site, temperature, latitude, organic matter content, and moisture content. This shortterm study involved single-year field and greenhouse research; however, it led to key insights into how and why long-term studies need to be carried out in the future to take full advantage of the impacts of trampling on the enhancement in the allelopathic potential of plants, along with suppression of weed growth, sustainably.…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest that the environmental conditions impacted the variations in the allelochemical exudation processes from the roots of the two weeds in response to mowing and varying trampling pressure. Similar to the outcome of this study, Yang et al [71] also reported that the root exudation rate of some plant species, such as Pinus koraiensis, Larix gmelinii, and Betula platyphylla, was influenced by environmental factors, including the site, temperature, latitude, organic matter content, and moisture content. This shortterm study involved single-year field and greenhouse research; however, it led to key insights into how and why long-term studies need to be carried out in the future to take full advantage of the impacts of trampling on the enhancement in the allelopathic potential of plants, along with suppression of weed growth, sustainably.…”
Section: Discussionsupporting
confidence: 88%
“…The few studies that have addressed temperature effects on tree root exudation employed either experimental soil warming of seedling cultures (Karst et al 2017; Uselman et al 2000;Yin et al 2013a, b) or compared trees of the same species at sites differing in mean temperature (Yang et al 2020). While most studies with trees indicate higher exudation under elevated temperatures, higher exudation at lower temperatures was also reported (Karst et al 2017;Yang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have addressed temperature effects on tree root exudation employed either experimental soil warming of seedling cultures (Karst et al 2017; Uselman et al 2000;Yin et al 2013a, b) or compared trees of the same species at sites differing in mean temperature (Yang et al 2020). While most studies with trees indicate higher exudation under elevated temperatures, higher exudation at lower temperatures was also reported (Karst et al 2017;Yang et al 2020). Due to the multitude of possible influential factors and the difficulties associated with measuring tree root exudation under field conditions, our understanding of climate warming effects on exudation is very limited (Wang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic factors that have been found to in uence root exudation rate include radiation through its in uence on photosynthesis (Nakayama and Tateno 2018), de ciency of nutrient elements such as P and N (Meier et al 2020;Yin et al 2014), soil moisture (Jakoby et al 2020;Preece et al 2018), and temperature (Yin et al, 2013a). The few studies that have addressed temperature effects on tree root exudation employed either experimental soil warming of seedling cultures (Karst et al 2017; Uselman et al 2000;Yin et al 2013 a, b,) or compared trees of the same species at sites differing in mean temperature (Yang et al 2020). While most studies indicate higher exudation under elevated temperatures, higher exudation at lower temperatures was also reported (Karst et al 2017;Yang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have addressed temperature effects on tree root exudation employed either experimental soil warming of seedling cultures (Karst et al 2017; Uselman et al 2000;Yin et al 2013 a, b,) or compared trees of the same species at sites differing in mean temperature (Yang et al 2020). While most studies indicate higher exudation under elevated temperatures, higher exudation at lower temperatures was also reported (Karst et al 2017;Yang et al 2020). Due to the multitude of possible in uential factors and the di culties associated with measuring tree root exudation under eld conditions, our understanding of climate warming effects on exudation is very limited.…”
Section: Introductionmentioning
confidence: 99%